Frequency- and Amplitude-Dependent Microbial Population Dynamics during Cycles of Feast and Famine - Merritt, Jason; Kuehn, Seppe (Physical review letters, 2018)
In nature microbial populations are subject to fluctuating nutrient levels. Nutrient fluctuations are important for evolutionary and ecological dynamics in microbial communities since they impact growth rates, population sizes, and biofilm formation. Here we use automated continuous-culture devices and high-throughput imaging to show that when populations of Escherichia coli are subjected to cycles of nutrient excess (feasts) and scarcity (famine) their abundance dynamics during famines depend on the frequency and amplitude of feasts. We show that frequency and amplitude dependent dynamics in planktonic populations arise from nutrient and history dependent rates of aggregation and dispersal. A phenomenological model recapitulates our experimental observations. Our results show that the statistical properties of environmental fluctuations have substantial impacts on spatial structure in bacterial populations driving large changes in abundance dynamics.